The Influence of Student Attitudes Towards Anti-Corruption and Deradicalization Education Based on the Principle of Amar Ma'ruf Nahi Munkar - Prayetno, Eko; Al Ayyubi, Ibnu Imam; Nurhikmah; Noerzanah, Firda; Asri, Muhammad Rizal (Journal of Education and Learning Sciences, 2023)
This study aims to analyze the influence of students' attitudes towards anti-corruption and deradicalization education based on the principle of amar ma'ruf nahi munkar. Using a mixed methods approach with an explanatory sequential design, this study begins with a quantitative method to measure the relationship between students' attitudes and anti-corruption and deradicalization education through the Spearman correlation test, which is continued with a qualitative method to explore students' attitudes more deeply through interviews and observations. The results of the quantitative analysis show that there is no significant relationship between students' attitudes towards anti-corruption and deradicalization education (sig. = 0.495 > 0.05) with a very weak negative correlation value (-0.143). This finding indicates that changes in students' attitudes do not have a significant effect on the effectiveness of anti-corruption and deradicalization education. However, the results of the interviews showed that students have a good conceptual understanding of amar ma'ruf nahi munkar, but its application in supporting anti-corruption and deradicalization education is still influenced by social and cultural factors. Therefore, a more contextual and experience-based approach in anti-corruption and deradicalization education is needed so that students are more proactive in implementing the principles of amar ma'ruf nahi munkar in everyday life.